Urban water cycle processes, management, and societal interactions: Crossing from crisis to sustainability - Zakaria N.A.; Ghani A.A.; Talib S.A.; Chan N.W.; Desa M.N.M. (American Society of Civil Engineers (ASCE), 2023)
The present paper highlights a combined research project among three universities, Universiti Sains Malaysia (USM), Universiti Teknologi MARA (UiTM), and Universiti Tenaga Nasional (UNITEN), in dealing with the water quality aspect of water security in Malaysia. Five subprojects were created to enhance the sustainability issue of water demand and supply. It is expected that the project as a whole will innovate new approaches and issues in urban water management in Malaysia. 2013 American Society of Civil Engineers.